Do older adults benefit from post-acute care following hospitalisation? A prospective cohort study at three Swiss nursing homes - Marion Thalmann; Thomas Tröster; Karina Fischer; Gabriela Bieri-Brüning; Patrick E. Beeler; Heike A. Bischoff-Ferrari; Michael Gagesch (Swiss Medical Weekly, 2020)
BACKGROUND